223Atrial fibrillation screen, management and guideline recommended therapy (AF SMART II) in the rural primary care setting: eHealth tools to support all stages of screening. (18th June 2020) - Orchard, J; Li, J; Freedman, B; Webster, R; Hespe, C; Gallagher, R; Neubeck, L; Lowres, N
Abstract: Funding Acknowledgements: National Heart Foundation of Australia: CVRN Grant and Vanguard Grant; investigator-initiated grant from Pfizer-BMS; AliveCor provided free devices BACKGROUND: Internationally, most atrial fibrillation (AF) management guidelines recommend screening for AF in people aged ≥65 years, as well as treatment with oral anticoagulants (OAC) for those at high stroke risk ( CHA2DS2-VA ≥2). However, in practice, gaps remain in both screening and treatment. In Australian general practice in 2017, the estimated rate of AF screening was 11%, and only about 60% of diagnosed AF patients received guideline-based OAC. Our 2018 screening study using eHealth tools in metropolitan general practices increased screening to 16% of eligible patients, leading to further refinement of the eHealth tools. PURPOSE: To investigate the impact of an AF screening program in rural general practices, using a suite of custom-designed eHealth tools designed to increase the proportion screened and treated for AF in accordance with guidelines. METHODS: General practices (n = 8) in rural New South Wales, Australia participated in the study between September 2018 – June 2019. General practitioners (GPs) and practice nurses conducted opportunistic screening of eligible patients (i.e. aged ≥65 years without existing AF diagnosis) using a smartphone electrocardiogram during practice visits. Practices were also provided with 1) an electronic screening prompt (which appeared when an eligible patient's file was opened); 2) electronic decision support based on ESC/Australian treatment guidelines; and 3) regular customised data reports aimed at quality improvement (Figure 1). A clinical audit tool was used to extract deidentified data from practices. RESULTS: A total of 3, 103 eligible patients (mean age 75.1 ± 6.8 years, 47% male) who attended the 8 practices during the study period were screened (median screening period 4.6 months). Practices screened a median of 35% of eligible patients (range 9-51% per practice), with 4/8 practices screening >40% of eligible patients. 36 (1.2%) new cases of AF were confirmed (mean age 77.0 years, 64% male, mean CHA2DS2-VA = 2.9). GPs (n = 22) screened 30% (range 1-182 per GP) of patients and nurses (n = 40) screened 70% (range 1-192 per nurse). OAC treatment rates of patients with AF with CHA2DS2-VA≥2 were 82% (screen-detected), 78% (clinically-detected during study period) and 75% (pre-existing AF), with no significant differences between groups. CONCLUSIONS: In the rural general practice setting, an AF screening program supported by eHealth tools resulted in 35% of eligible people screened, which is substantially higher than the 16% achieved in our previous study. Half the practices screened 40-50% of eligible patients, suggesting this may represent a 'ceiling' of patients captured by opportunistic AF screening programs. OAC treatment rates were higher than previous studies at baseline and were trending upwards during the study. eHealth tools, particularly including customised data reports as part of an audit and feedback system, may be a valuable addition to future screening programs.